Territorios relacionales. Propuesta conceptual para situar la movilidad sustentable en ciudades latinoamericanas - Jirón, Paola (2024)
The sustainable mobility approach emerged as a way of facing climate crisis, aiming to reduce CO2 emissions. However, despite its innovative character, the strong support from international organisations and consultants, as well as national and local governments, sustainable mobility does not fully capture the complexity of urban daily living, as the understanding of mobility is generally reduced to the diverse modes of transport and prioritising those with zero emissions. From a relational approach to territories, the daily mobility approach complements that of sustainable mobility and broadens its comprehension by introducing notions like mobility trajectories, interdependence, barriers and enablers. This approach provides more complex ways of understanding contemporary dwelling practices and territorial experiences. Based on mobile ethnographic research carried out in Santiago de Chile, in pandemic and post-pandemic times, this paper presents ways in which daily mobility can complement interventions linked to sustainable mobility. This approach can unveil the political conflicts that are intrinsically part of highly uneven cities, like those in Latin America, and particularly in Chile.